Systematic review of qualitative studies on participants in the decision-making process about the location of care of the elderly - Manuel Rich-Ruiz; Gema Serrano-Gemes; Rafael Serrano-del-Rosal (BMJ Open)
Objectives To understand who are the participants in the decision-making process about the location of care of the elderly.Design Systematic review of qualitative studies.Data sources The following databases were consulted: Web of Science, MEDLINE, Scopus, CINAHL, PsycINFO and SciELO (from the beginning until 29 November 2017). The bibliographical references in the studies that were finally included in the review were also searched.Study selection The studies had to deal with the decision-making process (already experienced by the participants) on the location of care of the elderly (adults who are 65 or older), had to use a qualitative methodology and had to be written in English or Spanish.Data extraction and synthesis A data extraction tool was used. Data analysis was conducted through the constant comparative method from Glaser and Strauss’ grounded theory.Results 46 studies were included in this review. Most of them were carried out in the USA, and in 21 of them the study population focused exclusively on the elderly. This review has found that there are many participants, with different roles and degrees of involvement, who may act jointly, separately or sequentially. These participants may be: the elders, family members, professionals and other relevant.Conclusions The main result of this review has been the variability found on how this decision is made, even varying the way of acting/perceiving the situation of the involved persons on certain occasions, simply due to the influence of some of the other groups of participants studied. Besides, this review has focused its results on the main participant in this process, the elders and how their family members interact with them when it comes to making this decision. This has allowed relevant results to be obtained about roles and degrees of involvement.PROSPERO registration number CRD42018084826.